HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN BAHASA ANAK USIA PRASEKOLAH DI YAYASAN PENDIDIKAN AN-NUR PASAR 1 SIDOMULYO, KECAMATAN BIRU-BIRU, KABUPATEN DELI SERDANG TAHUN 2024 - Natalia, Kristin - (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
One of the things that helps children’s speech and language development according to their age is parental education. A key component in raising children is establishing a parenting pattern, which connects the child's interactions with parents and encourages child development. This research aims to determine the relationship between parenting patterns and the language development of preschool children at the An-nur Pasar 1 Sidomulyo Education Foundation, Biru-biru District, Deli Serdang Regency in 2024. This research uses a cross-sectional design with a total sample approach. Thirty parents and children aged between four and six years took part in this study as respondents. Parent surveys and observations in the DDST-II format are tools used to collect information about children's parenting styles and language development. The statistical data analysis method used is the chi-square test. With a p-value of 0.000 (<0.05), the findings of this study indicate a relationship between preschool children's language development and their parents' parenting style. In terms of language development in children between the ages of 4 and 5, appropriate parenting practices can reduce the risk of delayed language acquisition. Therefore, under certain circumstances, parents need to discipline their children according to appropriate guidelines. Based on the research results, parenting patterns and the language development of preschool children at the An-nur Pasar 1 Sidomulyo Education Foundation, Biru-biru District, Deli Serdang Regency in 2024 have a relationship.